Effects of Violation of Equivalence Principle on UHE Neutrinos at IceCube in 4 Flavour Scenario (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
If weak equivalence principle is violated then different types of neutrinos would couple differentlywith gravity and that may produce a gravity induced oscillation for the neutrinos ofdifferent flavour. We explore here the possibility that very small violation of the principle ofweak equivalence (VEP) can be probed by ultra high energy neutrinos from distant astrophysicalsources. The very long baseline length and the ultra high energies of such neutrinos couldbe helpful to probe very small VEP. We consider a 4-flavour neutrino scenario (3 active + 1sterile) with both mass-flavour and gravity induced oscillations and compare the detection signaturesfor these neutrinos (muon tracks and shower events) with and without gravity inducedoscillations at a kilometer scale detector such as IceCube. We find that even very small VEP(∼ 10−42) can considerably affect the detected muon yield produced by UHE neutrinos fromdistant Gamma Ray Bursts (GRBs).